Mothers insights on food marketing of sweet products for children - Maulianti, Raden RDA; Februhartanty, Judhiastuty; Hanisa, Nisrina (World Nutrition Journal, 2024)
The 2018 Indonesian Basic Health Survey found that children aged 3-5 frequently consume sugary foods and drinks. Parental feeding practices significantly influence children's diets and health. Meanwhile, sophisticated food marketing targets parents, often promoting unhealthy foods high in sugar and challenging healthy feeding practices.